165k views
4 votes
Solve this quadratic equation using the quadratic formula. x^2 - 6x + 6 = 0

2 Answers

4 votes

Answer:

Explanation:

x= 6± √(6)^2-4(1)(6) /2(1)

=6± √12 /2

=6± 2√3 /2

=3± √3

User To E
by
5.0k points
7 votes

Answer: The required solution of the given quadratic equation is

x = 3 + √3 and x = 3 - √3.

Step-by-step explanation: We are given to solve the following quadratic equation using quadratic formula :


x^2-6x+6=0~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)

Quadratic formula : The solution of a quadratic equation of the form
ax^2+bx+c=0,~a\\eq 0 is given by


x=(-b\pm√(b^2-4ac))/(2a)

For the given quadratic equation (i), we have

a = 1, b = -6 and c = 6.

Therefore, the solution of equation (i) is given by


x\\\\\\=(-b\pm√(b^2-4ac))/(2a)\\\\\\=(-(-6)\pm√((-6)^2-4* 1*6))/(2*1)\\\\\\=(6\pm√(36-24))/(2)\\\\\\=(6\pm√(12))/(2)\\\\\\=(6\pm2√(3))/(2)\\\\=3\pm\sqrt3..

Thus, the required solution of the given quadratic equation is

x = 3 + √3 and x = 3 - √3.

User Thd
by
5.3k points